2019
DOI: 10.3390/md18010027
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative HPLC Analysis of Mycosporine-Like Amino Acids Extracted in Distilled Water for Cosmetical Uses in Four Rhodophyta

Abstract: Mycosporine-like amino acids (MAAs) have gained considerable attention as highly active photoprotective candidates for human sunscreens. However, more studies are necessary to evaluate the extraction efficiencies of these metabolites in cosmetic compatible solvents, as well as, their subsequent HPLC analysis. In the present study, MAA extraction using distilled water and 20% aqueous methanol in four Rhodophyta was investigated. Different re-dissolution solvents and a C8 and C18 columns were tested for the HPLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…Sinha et al [ 43 ] reported that shinorine and porphyra-334 were stable at 75 °C for up to 6 h. Coba et al [ 44 ] reported that MAAs were highly stable at room temperature during 24 h at pH 4.5–8.5 at 50 °C. Chaves-Peña et al [ 45 ] reported that the content of MAAs by water extraction and 20% methanol extraction was stable. When we extracted MAAs using methanol only, the content of the MAAs was stable despite of the extraction term ( Table 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sinha et al [ 43 ] reported that shinorine and porphyra-334 were stable at 75 °C for up to 6 h. Coba et al [ 44 ] reported that MAAs were highly stable at room temperature during 24 h at pH 4.5–8.5 at 50 °C. Chaves-Peña et al [ 45 ] reported that the content of MAAs by water extraction and 20% methanol extraction was stable. When we extracted MAAs using methanol only, the content of the MAAs was stable despite of the extraction term ( Table 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since MAAs are potential compounds to be used as sunscreens in cosmetic products, the extraction protocol must be optimized taking into account their physicochemical and absorption properties and must use environmentally friendly and inexpensive solvents [ 9 , 50 ]. Traditional extraction method is usually performed by a solid/liquid extraction from the raw material and is carried out on fresh or lyophilized samples with different temperature ranges [ 51 , 52 ].…”
Section: Mycosporine-like Amino Acidsmentioning
confidence: 99%
“…Nishida et al [ 33 ] applied a successive extraction method by using water and then methanol extraction, and spectrophotometric and HPLC analyses revealed that the yield of MAAs by 6 h water extraction was the highest among the tested conditions. Nevertheless, according to Chaves-Peña et al [ 32 ] the re-dissolution in pure methanol after dryness was the best option for the qualitative analysis of the most common MAAs in red algae in contrast to those reported by Karsten et al [ 31 ]. The efficient extraction in water has advantages for the use of MAAs in natural cosmetics since methanol is a reactive that is not allowed in natural cosmetics.…”
Section: Methodology For Extraction and Chemical Identification Ofmentioning
confidence: 98%
“…Consequently, Karsten et al [ 31 ] suggested that methanol should be avoided as a re-dissolution solvent for the HPLC sample preparation. The protocol for extraction and HPLC identification based on the C18 column by Karsten et al [ 31 ] is compared with protocols reported in three papers in this issue [ 32 , 33 , 34 ].…”
Section: Methodology For Extraction and Chemical Identification Ofmentioning
confidence: 99%
See 1 more Smart Citation